1985
DOI: 10.1086/131591
|View full text |Cite
|
Sign up to set email alerts
|

A luminosity function for star clusters in the Large Magellanic Cloud

Abstract: We determine a luminosity function for star clusters brighter than M ß = -4.5 in the LMC, from eye estimates of the integrated magnitudes of all clusters in two large regions of the LMC. The differential luminosity function rises monotonically toward faint magnitudes. Except for a higher abundance of bright clusters, it is qualitatively similar to the luminosity function for the open clusters in our Galaxy. It does not have the single-peaked shape that characterizes the globular-cluster systems of the Galaxy a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
43
0

Year Published

1988
1988
2011
2011

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 8 publications
(16 reference statements)
9
43
0
Order By: Relevance
“…Starting from the work by Elson & Fall (1985) on LMC SCs, empirical data from a large sample of spiral and irregular galaxies have shown that the Star Cluster Luminosity Function (SCLF) usually follows a power law, with a sharp turnover at faint magnitudes. In this section we analyse the LF profile of the SC candidate system in NGC 3370.…”
Section: Luminosity Functionsmentioning
confidence: 99%
“…Starting from the work by Elson & Fall (1985) on LMC SCs, empirical data from a large sample of spiral and irregular galaxies have shown that the Star Cluster Luminosity Function (SCLF) usually follows a power law, with a sharp turnover at faint magnitudes. In this section we analyse the LF profile of the SC candidate system in NGC 3370.…”
Section: Luminosity Functionsmentioning
confidence: 99%
“…This distribution can not be well fitted using any standard power-law luminosity function (see, e.g. Elson & Fall 1985, for the LMC star-clusters LF).…”
Section: Star-forming Regionsmentioning
confidence: 99%
“…However, power-law luminosity functions are generally associated with young stellar clusters, which have masses and sizes of GCs. And these younger populations generally reside in the LMC and in many starbursting and merging galaxies (e.g., Elson & Fall 1985;Meurer et al 1995;Whitmore et al 1997). And clearly, UGC 5981 does not have many young stellar cluster candidates, which are generally believed to have (V − I) < 0.5 color.…”
Section: Luminosity Function Of Globular Clustersmentioning
confidence: 99%